Assessment of blackfly (Diptera : Simuliidae) problem status and potential biological control agents along the Vaal and Orange Rivers in South Africa - Kappmeier, Karin (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.